Self-Sustainable Bio-methanol & Bio-char Coproduction from 2nd Generation Biomass Gasification - A.F. Amaral; G. Bozzano; C. Pirola; A.G. Goryunov; A. Chistyakov; F. Manenti (Chemical Engineering Transactions, 2017)
Methanol is an important intermediate in the synthesis of different chemicals. It is mainly produced by reforming of natural gas in centralized facilities with productive capacities on the order of 109 tons per day. Production of methanol from biomass suffers from the cost and logistics of the transportation of biomass and it has not yet maturated into commercial scale. The techno-economic feasibility of the co-production of bio- methanol and bio-char is assessed through detailed computer simulations using process simulator Aspen HYSYS® together with the gasification simulator GASDS. This work further elaborates the previous results on the bio-methanol production process, presenting particularities and updates on previously reported values. The production model is seen to be valid, with payback times that go from 3 to 6 years according to the capacity of the plant (100 to 1000 kt of biomass per year). Self-sustainability is possible but a 50/50 mix of producing and buying electricity yields the most economic choice.